Diagnostic value of serial measurement of C-reactive protein in serum and matrix metalloproteinase-9 in drainage fluid in the detection of infectious complications and anastomotic leakage in patients with colorectal resection - Kostić, Zoran; Panišić, Marina; Milev, Boško; Mijušković, Zoran; Slavković, Damjan; Ignjatović, Mile (Vojnosanitetski pregled, 2015)
Background/Aim. Postoperative infectious complications areone of the most important problems in surgical treatment of colorectalcancer (CRC), being present in up to 40% of patients.The aim of this paper was to establish the significance of serialmeasurement of C-reactive protein (CRP) in serum and matrixmetalloproteinase-9 (MMP-9) in drainage fluid for the detectionof infectious complications and anastomotic leakage (AL) in patientswith colorectal resection. Methods. CRP and MMP-9 valuesin serum and drainage fluid, respectively, were measured onthe first, third, fifth, and seventh postoperative day (POD) in 150patients with colorectal resection and primary anastomosis. Thevalues obtained were compared between the patients withoutcomplicatons and those with surgical site and remote infectionsand AL. Results. Surgical site infections (SSIs) were observed in41 (27.3%), and remote infections in 10 (6.7%) patients. Clinicallyevident AL was observed in 15 (10%) patients. In 82% ofthe patients with SSIs, serum CRP value on POD 5 exceeded 82mg/L, with 81% specificity. AL was reported in 85% and 92%of the patients on PODs 5 and 7, respectively, with CRP valuesof 77 mg/L and 90 mg/L, respectively. The specificity was 77%for POD 5 and 88% for POD 7. All the patients with CRP valuesexceeding 139 mg/L on POD 5 had some of SSIs and/orAL. The mean values of MMP-9 were not statistically differentbetween the group without complications (n = 99) and the groupwith AL (n = 15). Conclusion. Serial measurement of CRP isrecommended for screening of infectious complications of colorectalresection. Patients with CRP values above 139 mg/L onPOD 5 cannot be discharged from hospital, and require an intensivesearch for infectious complications, particularly AL.MMP-9 measurement in drainage fluid is not relevant in the detectionof AL in patients with colorectal resection.
Keywords: c-reactive protein; matrix metalloproteinases; anastomosis surgicall; postoperative complications; digestive system surgical procedures